MOTIVASI INTRINSIK YANG MEMPENGARUHI PEMILIHAN JURUSAN DAN UNIVERSITAS(Studi Pada Mahasiswa Baru Program Vokasi Universitas Indonesia Angkatan 2015) - Lusia, Amelita; Suciati, Pijar; Setiowati, Endang (Jurnal Vokasi Indonesia, 2015)
Globalization affects all aspects of life. This concept creates a paradigm borderless world, the world that does not know the limits of the territorial sovereignty of a nation / state. The impact of these conditions are helped create intense competition in various aspects of community life, including education. In the world of education, management can not be done conventionally alone, but requires a special ability that the output of education in accordance with market needs, both nationally and internationally. In addition to the need for change in the management of the educational institutions, educational institutions marketing issues was absolutely necessary due to the competition of universities / university higher. It was seen from the emergence of various colleges / universities that always offers the advantages of each. Colleges as providers of education services need to learn and have the initiative to improve customer satisfaction (students) because in general education is an ongoing process. Marketing educational institutions, almost similar to the marketing of the economy or government agencies engaged in services. However, if true, all marketing programs that have been carried out by the university is a factor and the reason students choose majors and certain universities? The answer could be yes, no, or may be it turns out there are other factors that influence greater than exposure to marketing. As expected the start of this study, there may be factors word of mouth (WOM) or electronic word of mouth (e- WOM) which also affect their choices, such as research Shahid, Et.al of the University of Lahore, Pakistan, which are listed in the journal IISTE 2012. The aim of this study was to identify common factors and other factors such as word of mouth, which is the reason the new students choose majors and certain universities. To identify them, the research will perform a quantitative approach through field surveys to students-freshmen at the University of Indonesia. Results of this research is the formulation of the deciding factors in choosing majors prospective students and universities, which is expected to help PR and marketing practitioners to develop a more effective marketing programs and was well received by the target objectives.